2014
DOI: 10.3109/13880209.2014.910237
|View full text |Cite
|
Sign up to set email alerts
|

The anti-inflammatory effect oftriphalain arthritic-induced rats

Abstract: Context: Triphala, an Indian Ayurvedic herbal formulation which contains Terminalia chebula Retz. (Combretaceae), Terminalia bellerica (Gaertn.) Roxb. (Combretaceae) and Emblica officinalis L. (Phyllanthaceae), is used for treating bowel-related complications, inflammatory disorders, and gastritis. Objective: To determine the anti-arthritic effect of triphala in arthritis-induced rats. For comparison purpose, the non-steroidal anti-inflammatory drug indomethacin was used. Materials and methods: Arthritis was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 46 publications
3
17
0
Order By: Relevance
“…Administration of Triphala (100 mg/kg b wt, i.p.) restored the activities/levels of antioxidant (SOD~75.6%, CAT~62.7%, GPx~55.8%, GST~82.1%, and GSH~72.7%), and decreased the lipid peroxidation in the paw tissues of arthritic rats [68]. A study on another monosodium urate crystal-induced arthritis model showed support for Triphala exhibiting antioxidant properties and decreasing inflammation.…”
Section: In Vivo Studiesmentioning
confidence: 94%
“…Administration of Triphala (100 mg/kg b wt, i.p.) restored the activities/levels of antioxidant (SOD~75.6%, CAT~62.7%, GPx~55.8%, GST~82.1%, and GSH~72.7%), and decreased the lipid peroxidation in the paw tissues of arthritic rats [68]. A study on another monosodium urate crystal-induced arthritis model showed support for Triphala exhibiting antioxidant properties and decreasing inflammation.…”
Section: In Vivo Studiesmentioning
confidence: 94%
“…Another study found that Triphala increased antioxidant levels and decreased lipid peroxidation in the tissues of arthritic rats. 69 …”
Section: Therapeutic Uses and Studiesmentioning
confidence: 99%
“…Our earlier reports showed that triphala extract had promising in vivo anti-inflammatory and anti-arthritic effects in adjuvant-induced arthritic rats (Kalaiselvan & Rasool 2015a). To explore anti-inflammatory molecular mechanisms, the present study focused on the inhibitory effects of the extract on pro-inflammatory cytokine, inflammatory enzyme, and inflammatory factor production by LPS-induced RAW 264.7, as well as their expression at the mRNA level.…”
Section: Discussionmentioning
confidence: 99%